SPECIFIC ASPECTS OF LABOR RESOURCE MANAGEMENT IN DIFFERENT COUNTRIES - Boltaboev, Dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Management of labor resources is different in the countries of the world. Although the goal is the same, the ways to achieve it are different. The article provides information on the management of labor resources in different countries and offers suggestions for their application.